The The Death of President Déby and the Resurgence of Another. - Hansen, Ketil Fred (Journal of Central and Eastern European African Studies, 2025)
This article discusses how Mahamat Déby managed to undertake a constitutional coup d’etat in Chad in April 2021. Speculations around the death of his father, Marchal and President Idriss Déby Itno, at the battlefield are central to understand the constitutional coup. Further the article discusses the various strategies and techniques Mahamat Déby used to transform his position from a transitional military president to an elected civil president with the ability to present himself also in the 2029 presidential elections.